Inclusión de cultivos de cobertura en planteos ganaderos intensivos - Uhaldegaray, Mauricio Gaston; Oderiz, Juan Agustin; Frasier, Ileana; Kloster, Nanci Soledad; Fernandez, Romina; Perez, Maria Micaela; Quiroga, Alberto Raul (Asociación Argentina de la Ciencia del Suelo, 2022)
Poster